Cultural Responsiveness in Group Psychotherapy: A Case study in The Netherlands - Maria van Noort (Forum for Group Psychotherapies and Processes)
Struck by the growing number of (in) voluntary immigrants worldwide and in my country The Netherlands, I want to describe if and how the term cultural responsiveness could be useful in Group Psychotherapy for clients from different cultural backgrounds.